Efficacy of traditional Chinese exercise for the treatment of pain and disability on knee osteoarthritis patients: a systematic review and meta-analysis of randomized controlled trials - Zhang, Shuaipan; Huang, Ruixin; Guo, Guangxin; Kong, Lingjun; Li, Jianhua; Zhu, Qingguang; Fang, Min (Frontiers in Public Health, 2023)
Objective: To evaluate the efficacy of Traditional Chinese Exercises (TCEs) in treating knee osteoarthritis (KOA). Methods: Four databases without language or publication status restrictions were searched until April 1, 2022. Based on the principle of Population, Intervention, Comparison, Outcomes and Study design, the researchers searched for randomised controlled trials of TCEs in treating KOA. The Western Ontario and McMaster Universities Osteoarthritis (WOMAC) pain was defined as the primary outcome, whereas stiffness and physical function were the secondary outcomes. Subsequently, two researchers conducted the process independently, and the data were analysed using the RevManV.5.3 software. Results: Overall, 17 randomised trials involving 1174 participants met the inclusion criteria. The synthesised data of TCEs showed a significant improvement in WOMAC pain score [standardised mean difference (SMD) = -0.31; 95% confidence interval (CI): -0.52 to -0.10; p = 0.004], stiffness score (SMD = -0.63; 95% CI: -1.01 to -0.25; p = 0.001) and physical function score (SMD = -0.38; 95% CI: -0.61 to -0.15; p = 0.001) compared with the control group. Sensitivity analyses were performed to determine the combined results’ stability, which was unstable after excluding articles with greater heterogeneity. A further subgroup analysis showed that it might be the reason for the heterogeneity of the different traditional exercise intervention methods. Additionally, it showed that the Taijiquan group improved pain (SMD = 0.74; 95% CI: -1.09 to 0.38; p < 0.0001; I2=50%), stiffness (SMD = - 0.67; 95% CI -1.14 to 0.20; p = 0.005) and physical function score (SMD = - 0.35; 95% CI: -0.54 to 0.16; p = 0.0003; I2= 0%) better than the control group. The Baduanjin group improved stiffness (SMD = - 1.30; 95% CI: -2.32 to 0.28; p = 0.01) and physical function (SMD = - 0.52; 95% CI: -0.97 to 0.07; p = 0.02) better than the control group. However, the other interventions showed no difference compared with the control group. Conclusions: This systematic review provides partial evidence of the benefits of TCEs for knee pain and dysfunction. However, due to the the heterogeneity of exercise, more high-quality clinical studies should be conducted to verify the efficacy.